Pendidikan Kesehatan tentang Pencegahan Infeksi Menular Seksual pada Remaja - Yetty Yuniarty (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2024)
Sexually Transmitted Infections (STIs) are diseases transmitted through sexual activity, whether vaginal, oral, or anal. However, these infections can also be transmitted outside of sexual contact, such as from mother to child (e.g., during birth or through breastfeeding) or through shared needles among drug users, as well as due to poor hygiene of the reproductive organs (http://dewibest.blogspot.com/2014/11/sap-kespro-pada-remaja.htm). STIs can be caused by bacteria, fungi, viruses, and protozoa. STIs are a significant public health issue globally, affecting both developed and developing countries. The actual incidence and prevalence of these infections are not precisely known in various countries (Fauziah Husna, 2020). According to the Centers for Disease Control (CDC) in 2022, the most frequently reported STIs worldwide include syphilis (including congenital syphilis), gonorrhea, chlamydia, chancroid, and HIV (Human Immunodeficiency Virus) (Niforatos, J.D., & Rothman, 2021).